Electricity prices during the energy crisis in Germany: The role of market power - Till Fladung; Anna Saile (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
During the energy crisis in 2022, electricity prices in Germany soared to unprecedented levels. To explore the drivers of the high electricity prices, we develop an electricity dispatch model that simulates hourly equilibrium prices under the assumption of perfect competition. We then extend this model to account for firms exercising market power. By comparing the outcomes of the perfect competition and Cournot competition models with actual market data, we demonstrate that market power may contributed to higher prices during the crisis, elevating them beyond what rising input costs alone would justify.
Keywords: Q41; Q43; L13; D43; L94; 330; Energy Economics; Market Power; Energy Crisis; Electricity Prices; Cournot Competition